Pengaruh Pemberian Kapsul Bawang Putih (Allium Sativum L.) Terhadap Kandungan Kolesterol, Trigliserida, HDL Dan LDL Darah Ayam Arab - I Nyoman Sukartha Jaya; Tjokorda Suwhendra Binetra; Ni Ketut Dewi Haryani (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2018)
The objective of this research was an evaluation of cholesterol total, triglyceride, HDL, and LDL concentration in blood of Arab chicken. Eighty (80) layer of Arab chicken were used to divided five treatment. Each treatment consisted of four replicates, so twenty experimental unit and each experimental unit consisted of four-layer Arab chicken. Doses of garlic capsules were 0 mg (control), 600 mg, 900 mg, 1200 mg, and 1500 mg. Data were analyzed by analysis of variance from CRD (Completely Randomized Design). When the difference exists among treatment, data obtained were further analyzed using Orthogonal Polynomial Contrast. The result of research showed that garlic (Allium sativum L.) capsules concentrations of blood Arab chicken, without significant effect on cholesterol total and LDL. 150 mg garlic capsules increased (P â‰¤ 0.01) 3.25 mg/dl HDL, and 33.0 mg/dl triglyceride concentrations of blood. Regression of HDL and triglyceride concentrations of blood was Y = 233.929 - 0.107 X, it means that increased 1 mg/dl HDL decreased 0.107 mg/dl triglyceride concentrations blood of Arab chicken.